Multi-component alloy catalyst for electrocatalytic carbon dioxide reduction and preparation method of multi-component alloy catalyst
Through the hierarchical porous structure of Cu-Zn-Sn-Bi multi-alloy catalyst, the problems of high catalyst cost, low activity and poor selectivity in the prior art are solved, efficient and stable carbon dioxide reduction is achieved, and the preparation process is simple and environmentally friendly.
Patent Information
- Application Number
- CN202411298426.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing electrocatalytic carbon dioxide reduction technology, the catalyst materials are costly, low in activity and poor selectivity, especially the copper-based catalysts have insufficient stability and selectivity, which hinders the practical application of this technology.
Cu-Zn-Sn-Bi multi-alloy catalyst is used to prepare Cu-Zn-Sn-Bi alloy with a graded porous structure by electrodeposition method to form a three-dimensional connected network structure, increasing the specific surface area and active sites of the catalyst, and improving catalysis. active.
High-efficiency electrocatalytic carbon dioxide reduction at low potentials was achieved, the Faraday efficiency of formic acid products reached 98%, and high stability was maintained. The Faraday efficiency was still above 90% after the cycle reaction, and the preparation method was simple and environmentally friendly.
Smart Images

Figure CN119287417A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-component alloy catalyst for electrocatalytic carbon dioxide reduction and also relates to a preparation method of the multi-component alloy catalyst. Background Art
[0002] Through electrochemical catalysis, CO 2 Converting CO2 into high-value hydrocarbon fuels is an effective means to solve climate problems and maintain global energy demand. Electrocatalytic CO2 reduction technology can achieve CO2 reduction under mild conditions using renewable electricity as a driving force. 2 The conversion and utilization of CO has the advantages of being environmentally friendly, low cost and simple operation. 2 Reduction reactions in aqueous solutions have high kinetic barriers and competing reactions with hydrogen evolution; therefore, developing highly active, highly selective, and highly stable catalysts is an important prerequisite for promoting the practical application of this technology.
[0003] Precious metal catalysts such as Au, Ag, Pt, and Pd can electrocatalyze CO with high selectivity. 2 Reduction reaction, but the cost of catalyst materials is too high; copper-based catalysts have good electrocatalytic CO 2 Reduction activity has been widely studied, but copper-based catalyst materials show low selectivity, hindering their practical application. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a multi-element alloy catalyst for electrocatalytic carbon dioxide reduction, which has high electrocatalytic CO 2 The present invention has high reduction activity, high selectivity for formic acid products and electrocatalytic stability; another object of the present invention is to provide a method for preparing the above-mentioned multi-element alloy catalyst.
[0005] Technical solution: The multi-element alloy catalyst described in the present invention is a Cu-Zn-Sn-Bi alloy; in the alloy, the atomic percentage of each metal element is: Cu: 20-70at%; Zn: 20-60at%; Sn: 0.1-15at%; Bi: 0.1-15at%.
[0006] Among them, the Cu-Zn-Sn-Bi alloy has a single-phase structure. It is difficult for existing copper-based multi-element alloys to form a single-phase structure. After forming a multi-phase structure, interphase corrosion is very likely to occur, so the electrocatalytic stability is poor.
[0007] The Cu-Zn-Sn-Bi alloy has a hierarchical porous structure, which includes macropores for forming a three-dimensional interconnected network structure and small pores formed on the walls of the macropores. The hierarchical porous structure can increase the specific surface area of the catalyst and increase the exposure of its active sites, thereby increasing the reaction rate and improving the catalytic activity.
[0008] Wherein, the pore wall is composed of Cu-Zn-Sn-Bi alloy particle accumulation.
[0009] Wherein, the size of the Cu-Zn-Sn-Bi alloy particles is 100-800 nm.
[0010] The preparation method of the multi-element alloy catalyst comprises the following steps:
[0011] (1) Preparation of copper salt, zinc salt, tin salt, bismuth salt, Na 3 C 6 H 5 O 7 NH 4 ) 2 SO 4 and H 3 BO 3 The electrodeposition solution;
[0012] (2) performing constant current electrodeposition in the electrodeposition solution of step (1) to prepare a Cu-Zn-Sn-Bi graded porous multi-element alloy;
[0013] (3) The multi-component alloy prepared in step (2) is washed and freeze-dried to obtain a multi-component alloy catalyst.
[0014] Wherein, in step (1), the copper salt is CuSO 4 ; The zinc salt is ZnSO 4 ; The tin salt is SnSO 4 The bismuth salt is Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O.
[0015] Among them, the concentrations of each compound in the electrodeposition solution are: CuSO 4 The concentration of ZnSO is 0.05~0.2M, 4 The concentration of SnSO is 0.05~0.2M, 4 The concentration of Bi(NH 3 ) 2 C 6 H 7 O7 ·H 2 The concentration of O is 0.001~0.02M, Na 3 C 6 H 5 O 7 The concentration of (NH 4 ) 2 SO 4 The concentration of H 3 BO 3 The concentration is 0.2~0.6M.
[0016] Wherein, in step (2), the current density of the constant current electrodeposition is 0.5-4A / cm 2 , the deposition time is 10 to 300 s.
[0017] Wherein, in step (3), after the electrodeposition is completed, the prepared multi-element alloy is immersed in ultrapure water to remove surface impurities, and the cleaning is repeated three times.
[0018] The ultrapure water immersion time shall not exceed 5 minutes each time.
[0019] Wherein, in step (3), the cleaned multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The Cu-Zn-Sn-Bi multi-element alloy of the present invention is used for electrocatalytic carbon dioxide reduction, showing high selectivity for formic acid products. At a relatively low potential (-1.0 V vs. RHE), the maximum Faraday efficiency of the formic acid product can reach 98%. At the same time, it also has high electrocatalytic stability. After 25 hours of cyclic reaction, the Faraday efficiency of the formic acid product is still maintained above 90%; (2) The method for preparing the Cu-Zn-Sn-Bi multi-element alloy of the present invention does not require the use of harsh reaction conditions such as high temperature and high pressure, is simple and easy, environmentally friendly, and can achieve ultra-fast preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The XRD pattern of the multi-element alloy prepared by the present invention;
[0022] Figure 2 is a scanning electron microscope image of the Cu-Zn-Sn multi-element alloy in Example 1;
[0023] Figure 3 is the EDS spectrum image of the Cu-Zn-Sn multi-element alloy in Example 1;
[0024] Figure 4is a scanning electron microscope image of the Cu-Zn-Sn-Bi multi-element alloy in Example 2;
[0025] Figure 5 is the EDS spectrum image of the Cu-Zn-Sn-Bi multi-element alloy in Example 2;
[0026] Figure 6 is a scanning electron microscope image of the Cu-Zn-Sn-Bi multi-element alloy in Example 3;
[0027] Figure 7 is the EDS spectrum image of the Cu-Zn-Sn-Bi multi-element alloy in Example 3;
[0028] Figure 8 The stability test of the electrocatalytic reduction of carbon dioxide to formic acid by the Cu-Zn-Sn-Bi multi-element alloy in Example 3;
[0029] Fig. 9 is a scanning electron microscope image of the Cu-Zn-Sn-Bi multi-element alloy in Example 4;
[0030] Fig.10 is the EDS spectrum image of the Cu-Zn-Sn-Bi multi-element alloy in Example 4;
[0031] Fig.11 is a scanning electron microscope image of the Cu-Zn-Bi multi-element alloy in Example 5;
[0032] Fig.12 This is the EDS spectrum image of the Cu-Zn-Bi multi-element alloy in Example 5;
[0033] Fig.13 is the XRD spectrum of the Cu-Sn-Bi multi-element alloy in Comparative Example 1;
[0034] Fig.14 is a scanning electron microscope image of the Cu-Sn-Bi multi-element alloy in Comparative Example 1;
[0035] Fig.15 is the XRD spectrum of the Cu-Zn-Sn-Bi multi-element alloy in Comparative Example 2;
[0036] Fig.16 is a scanning electron microscope image of the Cu-Zn-Sn-Bi multi-element alloy in Comparative Example 2;
[0037] Fig.17 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0038] Example 1
[0039] A method for preparing a multi-element alloy catalyst comprises the following steps:
[0040] (1) Configuration containing 0.05M CuSO 4 , 0.2M ZnSO 4 , 0.02M SnSO 4 , 0.1M Na 3 C 6 H 5 O 7 、0.2M(NH 4 ) 2 SO 4 and 0.2MH 3 BO 3 The electrodeposition solution;
[0041] (2) In the step (1), the electrodeposition solution was heated to 0.5 A / cm 2 The current density was set to be constant current electrodeposition, and the deposition time was 300 s to obtain Cu-Zn-Sn multi-element alloy;
[0042] (3) After the electrodeposition is completed, the prepared Cu-Zn-Sn multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Sn multi-element alloy catalyst.
[0043] The Cu-Zn-Sn multi-element alloy prepared by the above steps has a Cu content of 20 at%, a Zn content of 60 at%, and a Sn content of 20 at%. The Cu-Zn-Sn multi-element alloy has a three-dimensionally connected hierarchical porous structure, the pore size of the small pores is 50 to 200 nm, and the pore size of the large pores is 15 to 30 μm. The size of the Cu-Zn-Sn alloy particles grown on the pore wall skeleton is 100 to 200 nm. The crystal structure is body-centered cubic (BCC), and the XRD diagram is as follows: Figure 1 The scanning electron microscope image of the prepared multi-element alloy is shown in Figure 2 , the element energy spectrum is as follows Figure 3 . Figure 2 The electron microscope image shows the hierarchical porous structure. Figure 3 The percentage of each metal element can be obtained.
[0044] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Zn-Sn multi-element alloy in Example 1 is 18 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faradaic efficiency of formic acid product is 50.2%.
[0045] The specific process of the electrocatalytic carbon dioxide reduction performance test is as follows: in an H-type electrolytic cell, a Cu-Zn-Sn multi-element alloy self-supporting catalyst is used as the cathode, a platinum sheet electrode is used as the anode, an Ag / AgCl electrode is used as the reference electrode, and 0.5M KHCO 3 The solution is an electrolyte, and the electrocatalytic reaction is carried out at a potential of -1.0V (vs. RHE). A certain amount of cathode electrolyte is taken for nuclear magnetic resonance testing to obtain the content of the product formic acid. According to the formula
[0046] The Faradaic efficiency (FE) of formic acid production was calculated, where Ni is the number of electrons transferred and F is the Faraday constant (96485 C mol -1 ), n is the amount of product obtained from the NMR spectrum (mol), Q total is the total charge consumed during the electrolysis process (C).
[0047] Example 2
[0048] The preparation method of the multi-element alloy catalyst of the present invention comprises the following steps:
[0049] (1) Configuration containing 0.1M CuSO 4 , 0.2M ZnSO 4 , 0.016M SnSO 4 、0.004M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4M Na 3 C 6 H 5 O 7 、0.3M(NH 4 ) 2 SO 4 and 0.6MH 3 BO 3 The electrodeposition solution;
[0050] (2) In the electrodeposition solution of step (1), 1A / cm 2 The Cu-Zn-Sn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 1.50 s and a deposition time of 150 s.
[0051] (3) After the electrodeposition is completed, the prepared Cu-Zn-Sn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Sn-Bi multi-element alloy catalyst.
[0052] The Cu-Zn-Sn-Bi multi-element alloy prepared by the above steps has a Cu content of 53at%, a Zn content of 33at%, a Sn content of 11at%, and a Bi content of 3at%; has a three-dimensionally connected hierarchical porous structure, a pore size of 50-200nm for small pores, and a pore size of 30-70μm for large pores; a Cu-Zn-Sn-Bi alloy particle size grown on the pore wall skeleton is 200-700nm; its crystal structure is body-centered cubic (BCC), and the XRD diagram is as follows: Figure 1 The scanning electron microscope image of the prepared multi-element alloy is shown in Figure 4 , the element energy spectrum is as follows Figure 5 .
[0053] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Zn-Sn-Bi multi-element alloy of Example 2 is 12 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faradaic efficiency of formic acid production is 90%.
[0054] Example 3
[0055] The preparation method of the multi-element alloy catalyst of the present invention comprises the following steps:
[0056] (1) Configuration containing 0.1M CuSO 4 , 0.2M ZnSO 4 , 0.01M SnSO 4 、0.01M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4M Na 3 C 6 H 5 O 7 、0.4M(NH 4 ) 2 SO 4 and 0.3MH 3 BO 3 The electrodeposition solution;
[0057] (2) In the electrodeposition solution of step (1), 2A / cm 2 The Cu-Zn-Sn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 1.547 W and a deposition time of 30 s.
[0058] (3) After the electrodeposition is completed, the prepared Cu-Zn-Sn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Sn-Bi multi-element alloy catalyst.
[0059] The Cu-Zn-Sn-Bi multi-element alloy prepared by the above steps has a Cu content of 61at%, a Zn content of 28at%, a Sn content of 6at%, and a Bi content of 5at%; has a three-dimensionally connected hierarchical porous structure, a pore size of 50 to 200nm for small pores, and a pore size of 20 to 40μm for large pores; a Cu-Zn-Sn-Bi alloy particle size grown on the pore wall skeleton is 100 to 800nm; its crystal structure is body-centered cubic (BCC), and the XRD diagram is as follows: Figure 1 The scanning electron microscope image of the prepared multi-element alloy is shown in Figure 6 , the element energy spectrum is as follows Figure 7 .
[0060] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Zn-Sn-Bi multi-element alloy of Example 3 is 21 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faraday efficiency of formic acid product is 98%. At the same time, it also has high electrocatalytic stability. After 25h of cycle reaction, the Faraday efficiency of formic acid product is still maintained above 90%. Figure 8 shown.
[0061] Example 4
[0062] The preparation method of the multi-element alloy catalyst of the present invention comprises the following steps:
[0063] (1) Configuration containing 0.1M CuSO 4 , 0.2M ZnSO 4 , 0.006M SnSO 4 、0.014M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4M Na 3 C 6 H 5 O 7 、0.6M(NH 4 ) 2 SO 4 and 0.3MH 3 BO 3 The electrodeposition solution;
[0064] (2) In the electrodeposition solution of step (1), 2A / cm 2 The Cu-Zn-Sn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 10 s.
[0065] (3) After the electrodeposition is completed, the prepared Cu-Zn-Sn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Sn-Bi multi-element alloy catalyst.
[0066] The Cu-Zn-Sn-Bi multi-element alloy prepared by the above steps has a Cu content of 42at%, a Zn content of 45at%, a Sn content of 4at%, and a Bi content of 9at%; it has a three-dimensionally connected hierarchical porous structure, the pore size of the small pores is 50-200nm, and the pore size of the large pores is 20-30μm; the size of the Cu-Zn-Sn-Bi alloy particles grown on the pore wall skeleton is 100-400nm; its crystal structure is body-centered cubic (BCC), and the XRD diagram is as follows: Figure 1 The scanning electron microscope image of the prepared multi-element alloy is shown in Fig. 9 , the element energy spectrum is as follows Fig.10 .
[0067] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Zn-Sn-Bi multi-element alloy of Example 4 is 11 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faradaic efficiency of formic acid product is 88%.
[0068] Example 5
[0069] A method for preparing a multi-element alloy catalyst comprises the following steps:
[0070] (1) Configuration containing 0.2M CuSO 4 , 0.15M ZnSO 4 、0.02M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4MNa 3 C 6 H 5 O 7 、0.25M(NH 4 ) 2 SO 4 and 0.3MH3 BO 3 The electrodeposition solution;
[0071] (2) In the electrodeposition solution of step (1), 2A / cm 2 The Cu-Zn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 1.547 W and a deposition time of 30 s.
[0072] (3) After the electrodeposition is completed, the prepared Cu-Zn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Bi multi-element alloy catalyst.
[0073] The Cu-Zn-Bi multi-element alloy prepared by the above steps has a Cu content of 65at%, a Zn content of 20at%, and a Bi content of 15at%; has a three-dimensionally connected hierarchical porous structure, a pore size of 50-200nm for small pores, and a pore size of 20-40μm for large pores; a Cu-Zn-Bi alloy particle size grown on the pore wall skeleton is 100-600nm; its crystal structure is body-centered cubic (BCC), and the XRD diagram is as follows: Figure 1 The scanning electron microscope image of the prepared Cu-Zn-Bi multi-element alloy is shown in Fig.11 , the element energy spectrum is as follows Fig.12 .
[0074] The electrocatalytic carbon dioxide reduction performance test showed that the current density of the Cu-Zn-Bi multi-element alloy of Example 5 at a potential of -1.0 V (vs. RHE) was 11 mA / cm 2 , the Faradaic efficiency of formic acid product is 87%.
[0075] By comparing Examples 4 to 5, it can be seen that the continued increase in the Bi element content no longer has an effect on the catalytic activity of the catalyst.
[0076] Comparative Example 1
[0077] A method for preparing a multi-element alloy catalyst comprises the following steps:
[0078] (1) Configuration containing 0.1M CuSO 4 , 0.01M SnSO 4 、0.01M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4MNa 3 C 6 H5 O 7 、0.4M(NH 4 ) 2 SO 4 and 0.3MH 3 BO 3 The electrodeposition solution;
[0079] (2) In the electrodeposition solution of step (1), 2A / cm 2 The Cu-Sn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 1.547 W and a deposition time of 30 s.
[0080] (3) After the electrodeposition is completed, the prepared Cu-Sn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Sn-Bi multi-element alloy catalyst.
[0081] The Cu-Sn-Bi multi-element alloy prepared by the above steps has a Cu content of 72at%, a Sn content of 21at%, and a Bi content of 7at%; it has a three-dimensionally connected hierarchical porous structure, the pore size of the small pores is 50-200nm, and the pore size of the large pores is 16-35μm; the size of the Cu-Sn-Bi alloy particles grown on the pore wall skeleton is 300-650nm; its crystal structure is a body-centered cubic phase of Cu6Sn5 and a metal Sn phase structure, and the XRD diagram is as follows Fig.13 The scanning electron microscope image of the prepared multi-element alloy is shown in Fig.14 .
[0082] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Sn-Bi multi-element alloy in comparative example 1 is 16 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faradaic efficiency of formic acid product is 62%.
[0083] Comparative Example 2
[0084] A method for preparing a multi-element alloy catalyst comprises the following steps:
[0085] (1) Configuration containing 0.1M CuSO 4 , 0.2M ZnSO 4 , 0.01M SnSO 4 、0.01M Bi(NH 3 ) 2 C 6 H 7 O 7 ·H 2 O, 0.4M Na 3C 6 H 5 O 7 and 0.3MH 3 BO 3 The electrodeposition solution;
[0086] (2) In the electrodeposition solution of step (1), 2A / cm 2 The Cu-Zn-Sn-Bi multi-element alloy was prepared by constant current electrodeposition with a current density of 1.547 W and a deposition time of 30 s.
[0087] (3) After the electrodeposition is completed, the prepared Cu-Zn-Sn-Bi multi-element alloy is immersed in ultrapure water to remove surface impurities, and the washing is repeated three times; each ultrapure water immersion time does not exceed 5 minutes; the washed multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours to obtain a Cu-Zn-Sn-Bi multi-element alloy catalyst.
[0088] The Cu-Zn-Sn-Bi multi-element alloy prepared by the above steps has a Cu content of 49at%, a Zn content of 34at%, a Sn content of 6at%, and a Bi content of 11at%. The morphology is a film with a granular rough surface and no porous structure. The size of the Cu-Zn-Sn-Bi alloy particles grown on the surface is 200-800nm. The crystal structure is a body-centered cubic phase of CuZn and a metallic Bi phase structure. The XRD diagram is as follows: Fig.15 The scanning electron microscope image of the prepared multi-element alloy is shown in Fig.16 .
[0089] The electrocatalytic carbon dioxide reduction performance test shows that the current density of the Cu-Zn-Sn-Bi multi-element alloy of comparative example 2 is 14 mA / cm at a potential of -1.0 V (vs. RHE). 2 , the Faradaic efficiency of formic acid product is 76%.
Claims
1. A multi-element alloy catalyst for electrocatalytic carbon dioxide reduction, characterized in that: The catalyst is a Cu-Zn-Sn-Bi alloy; In the alloy, the atomic percentage of each metal element is: Cu: 20-70 at%; Zn: 20-60 at%; Sn: 0.1-15 at%; Bi: 0.1~15at%.
2. The multi-element alloy catalyst according to claim 1, characterized in that: The Cu-Zn-Sn-Bi alloy presents a hierarchical porous structure, which includes macropores for forming a three-dimensional interconnected network structure and small pores formed on the pore walls of the macropores.
3. The multi-element alloy catalyst according to claim 1, characterized in that: The pore wall is composed of Cu-Zn-Sn-Bi alloy particles; the size of the Cu-Zn-Sn-Bi alloy particles is 100-800nm.
4. The method for preparing the multi-element alloy catalyst according to claim 1, characterized in that: The steps include: (1) preparing an electrodeposition solution containing copper salt, zinc salt, tin salt, bismuth salt, Na3C6H5O7, (NH4)2SO4 and H3BO3; (2) performing constant current electrodeposition in the electrodeposition solution of step (1) to prepare a Cu-Zn-Sn-Bi graded porous multi-element alloy; (3) The multi-component alloy prepared in step (2) is washed and freeze-dried to obtain a multi-component alloy catalyst.
5. The method for preparing a multi-element alloy catalyst according to claim 4, characterized in that: In step (1), the copper salt is CuSO4; the zinc salt is ZnSO4; the tin salt is SnSO4; and the bismuth salt is Bi(NH3)2C6H7O7·H2O.
6. The method for preparing a multi-component alloy catalyst according to claim 5, characterized in that: In the electrodeposition solution, the concentrations of the compounds are: CuSO4 is 0.05-0.2M, ZnSO4 is 0.05-0.2M, SnSO4 is 0.001-0.02M, Bi(NH3)2C6H7O7·H2O is 0.001-0.02M, Na3C6H5O7 is 0.1-0.4M, (NH4)2SO4 is 0.2-0.6M, and H3BO3 is 0.2-0.6M.
7. The method for preparing a multi-element alloy catalyst according to claim 4, characterized in that: In step (2), the current density of the constant current electrodeposition is 0.5 to 4 A / cm 2 , the deposition time is 10 to 300 s.
8. The method for preparing a multi-element alloy catalyst according to claim 4, characterized in that: In step (3), after the electrodeposition is completed, the prepared multi-element alloy is immersed in ultrapure water and repeatedly washed.
9. The method for preparing a multi-element alloy catalyst according to claim 8, characterized in that: Each immersion in ultrapure water should not exceed 5 minutes.
10. The method for preparing a multi-element alloy catalyst according to claim 4, characterized in that: In step (3), the cleaned multi-element alloy is placed in a vacuum freeze dryer and freeze-dried for more than 2 hours.